Effect and satisfaction analysis of perioperative nursing in secondary hyperparathyroidism - Xiaodong Feng; Ting Bi; Wei Li; Yang Tong; Yufu Tang; Sijia Bai; Guangming Cheng; Jie Qin; Wei Zhang (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the effect and satisfaction of perioperative nursing in secondary hyperparathyroidism patients. Method: The study was conducted at the General Hospital of Northern Theatre Command, Shenyang, China, from January 2021 to December 2022, and comprised secondary hyperparathyroidism patients who underwent parathyroidectomy. They were randomised into study group SG receiving preoperative, intraoperative and postoperative nursing, and control group CG receiving routine nursing. The length of hospital stay, levels of intact parathyroid hormone, calcium and alkaline phosphatase levels, incidence of complications, quality of life and nursing satisfaction of the patients in the two groups were compared. Data was analysed using SPSS 21. Results: Of the 100 patients, 50(50%) were in SG group; 26(52%) males and 24(48%) females with mean age 50.21±5.08 years. The other 50(50%) patients were in the CG group; 25(50%) males and as many females with mean age 50.19±5.02 years. Compared to CG subjects, the length of hospital stay was shorter, intact parathyroid hormone, calcium and alkaline phosphatase levels were lower, complications were fewer, and quality of life and nursing satisfaction scores were higher among SG subjects (p<0.05). Conclusion: Perioperative nursing of secondary hyperparathyroidism patients undergoing parathyroidectomy could accelerate postoperative recovery, improve serum biochemical indicators, and reduce the incidence of complications. Keywords: Secondary hyperparathyroidism, Perioperative nursing, Complication, Biochemical indicators.